ANT 2002/03: AWI airborne Radio-Echo Sounding Data over western DML, Jutulstraumen, Coats Land and the EDML and Dome Fuji ice core site (EPICA, SEAL, and VISA projects) - Heinrich Miller; Wilfried Jokat; Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system during the Antarctic season of 2002/03. The profiles extend across the western Dronning Maud Land Jutulstraumen, Coats Land and on the plateau along the EDML and Dome Fuji ice core site. Additionally, the profiles cover the Riiser Larsen Ice Shelf. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.